(untitled) (Annals of Medical Research, 2021)
Aim: The aim of the study is to evaluate the effect of adding hypertonic saline to conventional transforaminal epidural steroid injections (TFESIs) in the management of patients with lumbar disc herniation (LDH) with radicular pain.Material and Methods: The study included 57 patients with L4–L5 LDH treated with TFESI. The patients were divided into two groups: the hypertonic (n = 29) and conventional groups (n = 28). The conventional group was administered with triamcinolone, bupivacaine, and isotonic saline. Subsequently, the hypertonic group was administered with triamcinolone, bupivacaine, and 10% hypertonic saline. The patients were followed up using the numeric rating scale (NRS) and Oswestry disability index (ODI). Substantial and moderate responder ratios were achieved using NRS. Outcome measurements were performed at baseline, one, three, six, and nine months. Complications were recorded in both groups.Results: TFESI with or without adjuvant hypertonic saline was found to be effective by achieving a significant reduction in NRS and ODI scores during the overall follow-up period. Reduction of NRS scores at six- and nine-month follow-up and ODI scores at nine-month follow-up in the hypertonic group were significantly higher than those in the conventional group. Moreover, substantial response in the hypertonic group was significantly higher than that in the conventional group. Both groups had no complications. Conclusion: The administration of adjuvant 10% hypertonic saline to transforaminal injections enhances the treatment efficacy by increasing pain reduction and improving the quality of life in the late follow-up period.